1991
DOI: 10.1111/j.1574-6968.1991.tb04553.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of azasqualene on hopanoid biosynthesis and ethanol tolerance ofZymomonas mobilis

Abstract: Summary The effect of 2‐aza‐2,3‐dihydrosqualene (azasqualene) on growth and hopanoid content of Zymomonas mobilis was investigated. Concentrations of 4–7 μM azasqualene resulted in a diminishment of growth and hopanoid content of cells with a simultaneous accumulation of squalene. The inhibitory effect of azasqualene was enhanced by ethanol. Furthermore, the importance of hopanoids for the ethanol tolerance of Z. mobilis was demonstrated by an increased growth inhibition of cells with reduced hopanoid content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…As found for the eukaryotic oxidosqualene cyclases, conserved aspartate residues (Asp-376 and Asp-377) are important for the catalytic activity of SHC and it has been suggested that these amino acids are present in order to stabilise the charge of intermediate cations generated during the cyclization. 1356 2-Aza-2,3-dihydrosqualene has been found to inhibit SHC, 1357 which would certainly be consistent with such a mechanism. SHC has been purified and characterised from Alicyclobacillus acidocaldarius (Bacillus acidocaldarius) 1358 and Rhodopseudomonas palutsris.…”
Section: Biosynthesis Of Hopanoid Triterpenes From Isopentenyl Pyroph...mentioning
confidence: 66%
“…As found for the eukaryotic oxidosqualene cyclases, conserved aspartate residues (Asp-376 and Asp-377) are important for the catalytic activity of SHC and it has been suggested that these amino acids are present in order to stabilise the charge of intermediate cations generated during the cyclization. 1356 2-Aza-2,3-dihydrosqualene has been found to inhibit SHC, 1357 which would certainly be consistent with such a mechanism. SHC has been purified and characterised from Alicyclobacillus acidocaldarius (Bacillus acidocaldarius) 1358 and Rhodopseudomonas palutsris.…”
Section: Biosynthesis Of Hopanoid Triterpenes From Isopentenyl Pyroph...mentioning
confidence: 66%
“…Genes in the fatty acid and hopanoid biosynthetic pathways are upregulated in ZM4 compared to AcR (Additional File 8A). Hopanoids have been found in a variety of bacteria including Z. mobilis and are reported to protect against the toxic effects of ethanol (Flesch and Rohmer, 1989; Hermans et al, 1991; Horbach et al, 1991; Shigeri et al, 1991; Welander et al, 2009). For example, they have also been reported to play a role in Rhodopseudomonas palustris membrane integrity and pH homeostasis (Welander et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…There is a large body of evidence supporting a possible role of apolar polyisoprenoids as membrane regulators. To begin with, studies about lycopene contents of Haloferax volcanii and Zymomonas mobilis show that apolar polyisoprenoid levels are growth phase dependent, with increased synthesis in stationary phase [165,166]. The high energy-cost of lycopene synthesis, i.e., 24 ATP and 12 NADH per molecule, suggests that the presence of squalene-type isoprenoids must be essential for cell viability in the stationary phase.…”
Section: Apolar Polyisoprenoidsmentioning
confidence: 99%